2020
DOI: 10.3961/jpmph.20.035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Out-of-pocket Payment, Catastrophic Health Expenditure and the Related Socioeconomic Inequality in Peru: A Comparison Between 2008 and 2017

Abstract: Describe out-of-pocket payment (OOP) and the proportion of Peruvian households with catastrophic health expenditure (CHE) and evaluate changes in socioeconomic inequalities in CHE between 2008 and 2017. Methods: We used data from the 2008 and 2017 National Household Surveys on Living and Poverty Conditions (ENAHO in Spanish), which are based on probabilistic stratified, multistage and independent sampling of areas. OOP was converted into constant dollars of 2017. A household with CHE was assumed when the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…The results from examining the protective effect of different health insurance schemes (Additional file 7) suggest that health insurance in LMICs did not consistently offer a higher degree of FRP. Even though insurance lowered CHE in six studies (in Ghana, Iran, Peru, Thailand and Viet Nam) [34,[52][53][54][55][56], three studies reported higher CHE in India, Iran and Kenya [57][58][59], and another three studies reported not necessarily lower CHE in Colombia, Mexico and Vietnam [60][61][62]. Again, two of these studies showed mixed results: insured households incurred higher CHE but lower impoverishment than the noninsured in India [57], and CHE decreased but impoverishment increased just after launching the Health Transformation Plan in Iran [56].…”
Section: Frp Through Health Insurancementioning
confidence: 99%
“…The results from examining the protective effect of different health insurance schemes (Additional file 7) suggest that health insurance in LMICs did not consistently offer a higher degree of FRP. Even though insurance lowered CHE in six studies (in Ghana, Iran, Peru, Thailand and Viet Nam) [34,[52][53][54][55][56], three studies reported higher CHE in India, Iran and Kenya [57][58][59], and another three studies reported not necessarily lower CHE in Colombia, Mexico and Vietnam [60][61][62]. Again, two of these studies showed mixed results: insured households incurred higher CHE but lower impoverishment than the noninsured in India [57], and CHE decreased but impoverishment increased just after launching the Health Transformation Plan in Iran [56].…”
Section: Frp Through Health Insurancementioning
confidence: 99%
“…When designing and implementing financing protection policies, it is crucial to consider demographics, vulnerable groups, and diseases that exhibit higher likelihoods of CHE [ 8 , 28 , 32 ]. In addition to the effort to decrease the occurrence of CHE, there is a need to reduce socioeconomic inequality concerning the burden of CHE among various subpopulations by ensuring comprehensive coverage for all and facilitating access to health resources and services [ 33 ]. Based on the findings of this study, living in an urban area, having a higher wealth in-dex, possessing health insurance coverage, and having employed family members, an employed household head, and a literate household head are all associated with a reduced likelihood of experiencing CHE.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, it may be valid to assume that all transactions where patients report being not given any information about official co-payments rates or fees are informal. (21) (5) (22) Future efforts to measure informal payments may consider assessment of respondents’ awareness of entitlements and expected payments.…”
Section: Discussionmentioning
confidence: 99%